1998
DOI: 10.1161/01.atv.18.9.1498
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-6 in Atherosclerotic Lesions of Male ApoE-Knockout Mice

Abstract: Abstract-Increased levels of interleukin-6 (IL-6) have been proposed to contribute to a number of pathological disorders, including osteoporosis and Alzheimer's disease. In human atherosclerotic lesions, IL-6 protein and mRNA have been detected, although the role of IL-6 in plaque formation is unknown. We have examined the expression pattern of IL-6 mRNA and secreted protein in male apolipoprotein E-knockout (apoE-KO) mice aortas. Furthermore, we have evaluated the effects of 17␤-estradiol (E2), a vasculoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 42 publications
8
72
0
Order By: Relevance
“…8 -10 IL-6 is increased in atherosclerotic lesions in apoE-KO mice in association with the infiltrating macrophages. 11 In human AAAs, the circulating level of IL-6 has been reported to be elevated 12 and positively correlated with aortic diameter expansion. 13 Consistent with these observations, we showed that ex vivo secretion of IL-6 from the aneurysmal segment of the aorta was increased compared to the aortic arch in Ang II-treated mice and to the aortic segments from the vehicle-treated mice ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 -10 IL-6 is increased in atherosclerotic lesions in apoE-KO mice in association with the infiltrating macrophages. 11 In human AAAs, the circulating level of IL-6 has been reported to be elevated 12 and positively correlated with aortic diameter expansion. 13 Consistent with these observations, we showed that ex vivo secretion of IL-6 from the aneurysmal segment of the aorta was increased compared to the aortic arch in Ang II-treated mice and to the aortic segments from the vehicle-treated mice ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of IL-6 was measured at different time points by using a commercially available murine IL-6 enzyme-linked immunosorbent assay (Biotrak IL-6 ELISA kit; Amersham Life Sciences, Arlington Heights, IL) as described. 11 The IL-6 values were normalized to the weight of the aortic tissue segment and expressed as pg/ml per mg tissue.…”
Section: Ex Vivo Aorta Organ Culture and Il-6 Secretion Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…37 Studies in apoE knockout mice that develop atherosclerotic plaques in the aorta also show that elevated levels of IL-6 mRNA predominate in the plaque area compared with normal mice. 38 Thus, IL-6 may damage the endothelium and lead to the initiation of atherosclerosis, especially in areas of the vascular system that are predisposed to atherosclerosis because of decreased shear stress with turbulent blood flow such as the carotid bifurcation.…”
Section: Discussionmentioning
confidence: 99%
“…25 Studies in ApoE-knockout mice, that spontaneously develop systemic atherosclerosis, also show elevated levels of IL-6 mRNA in the plaque area compared with normal mice. 26 On the other hand, several studies have investigated the possible clinical significance of IL-6 gene variants and analysed their association with atherosclerotic disorders, including carotid atherosclerosis, CAD, and abdominal aortic aneurysm. 25,27,28 Following these observations, our study was designed in order to analyse the association between a common polymorphism of the IL-6 gene promoter and EH.…”
Section: Discussionmentioning
confidence: 99%